2004
DOI: 10.1016/j.jcrs.2003.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Surgically induced corneal refractive change following glaucoma surgery

Abstract: Despite larger flap size and surgical area, nonpenetrating trabecular surgeries induced less astigmatism than trabeculectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
22

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 18 publications
3
53
0
22
Order By: Relevance
“…76 Most studies have noted these corneal changes to be transient 74,77,78 but significant change can persist up to six months following surgery. 75,76 Trabeculectomy for glaucoma can cause significant corneal change, which is typically a steepening in the vertical meridian, leading to an increase in regular WTR [79][80][81] and irregular astigmatism. 82 The size of the incision appears to be correlated to the amount of induced astigmatism with smaller incisions (as used in 'microtrabeculectomy' procedures) leading to a smaller astigmatic change.…”
Section: Astigmatism Resulting From Ocular Surgerymentioning
confidence: 99%
“…76 Most studies have noted these corneal changes to be transient 74,77,78 but significant change can persist up to six months following surgery. 75,76 Trabeculectomy for glaucoma can cause significant corneal change, which is typically a steepening in the vertical meridian, leading to an increase in regular WTR [79][80][81] and irregular astigmatism. 82 The size of the incision appears to be correlated to the amount of induced astigmatism with smaller incisions (as used in 'microtrabeculectomy' procedures) leading to a smaller astigmatic change.…”
Section: Astigmatism Resulting From Ocular Surgerymentioning
confidence: 99%
“…A total of 24 articles were excluded, including 9 full reports [16,17,18,19,20,21,22,23,24], and 15 meeting abstracts (see Appendix 1). Out of them, 17 randomized controlled trials were included in the present meta-analysis, 14 published in full form [25,26,27,28,29,30,31,32,33,34,35,36,37,38] and 3 published in abstract form (see Appendix 2).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] The use of intraoperative MMC during deep sclerectomy significantly reduced the postoperative IOP and increased the success rate of the procedure and the probability of achieving lower target IOPs. 12,[14][15][16] However, to the best of our knowledge, no other study has reported data about deep sclerectomy augmented with MMC in eyes with a previously failed trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] As an initial surgery, deep sclerectomy may offer success rates comparable to trabeculectomy and minimize the risk of postoperative complications. [8][9][10][11][12][13] Recently, the adjunctive use of MMC in deep sclerectomy has been reported to be safe and to improve the surgical results. 12,[14][15][16] Although studies have been performed on the efficacy of trabeculectomy with MMC in eyes that underwent previous filtering procedures, [4][5][6][7] to the best of our knowledge, no study has been published on the success rate and safety of deep sclerectomy augmented with MMC in these eyes.…”
Section: Introductionmentioning
confidence: 99%